TEACHER'S SUPPORT FOR PUPIL'SENGLISH GRAMMAR LEARNING(A CASE STUDY OF AN ELEMENTARY SCHOOL IMPLEMENTING MUF FRAMEWORK IN TEACHING GRAMMAR IN BANDUNG) - Edwar Mohamad Kartakusumah, - (2010)
Abstract This study investigated the types of teacher's support in assisting pupils' English grammar learning and the reason underlying the use of those types of support. It was a qualitative research which was conducted at one of the state-owned elementary schools in western Bandung. The participant of this study was an English teacher of grade 5 implementing MUF framework in teaching grammar. The data for this study are gathered through classroom observation and interview. The finding revealed that the teacher adopting MUF framework employed three types of support in assisting her pupils' English grammar learning, namely teacher's language, techniques, and children themselves. The teacher modified her language to make it appropriate for pupils using repetition, comprehension check, shifting to L1, expansion, clarification request, and gesture. She employed several techniques in assisting her pupils, namely sequence, focusing on things, prompting, giving feedback, using visual support, providing clear context, modeling, and creating interesting activity. She also utilized the pupils to practice the new language with other pupils. Furthermore, in supporting her pupils learning, she also had some reasons which were taken into account when using those types of support. From these findings, it is recommended that further study be conducted in a longer period to solve the lack of collecting complete data and comprehensive observation and be focused on teacher's support which empowers pupils themselves to support each other.